High Frequency Techniques An Introduction to RF and Microwave Engineering / Joseph F. White. - White, Joseph F. (Wiley InterScience electronic collection., 2003)
A practical guide for today's wireless engineerHigh Frequency Techniques: An Introduction to RF and Microwave Engineering is a clearly written classical circuit and field theory text illustrated with modern computer simulation software. The book's ten chapters cover: *The origins and current uses of wireless transmission *A review of AC analysis, Kirchhoff's laws, RLC elements, skin effect, and introduction to the use of computer simulation software*Resonators, Q definitions, and Q-based impedance matching *Transmission lines, waves, VSWR, reflection phenomena, Fano's reflection bandwidth limits, telegrapher, and impedance transformation equations*Development and in-depth use of the Smith Chart *Matrix algebra with Z, Y, ABCD, S, and T matrix applications*An unusually thorough introduction to electromagnetic field theory, step-by-step development of vector calculus, Maxwell's equations, waveguides, propagation, and antennas*Backward wave, branch line, rat race and Wilkinson couplers, impedance measurements, and detailed even and odd mode analysis*Filter designs for Butterworth, Chebyshev, Bessel and elliptic responses, Kuroda's identities, Richards's transformation, and computer optimized designs*Transistor amplifier design using Unilateral Gain, Simultaneous Match, Available Gain and Operating Gain approaches, insuring stability, cascading stages, broadbanding, noise theory, and intermodulation effectsUsing informal language, High Frequency Techniques takes the reader step-by- step through RF and microwave theory and design, providing a lasting practical reference for the practicing wireless engineer.@.